2019
DOI: 10.1186/s13019-019-0908-9
|View full text |Cite
|
Sign up to set email alerts
|

A case report: Veno-venous extracorporeal membrane oxygenation for severe blunt thoracic trauma

Abstract: Introduction The use of veno-venous extracorporeal membrane oxygenation (VV-ECMO) in trauma patients has been controversial, but VV-ECMO plays a crucial role when the lungs are extensively damaged and when conventional management has failed. VV-ECMO provides adequate tissue oxygenation and an opportunity for lung recovery. However, VV-ECMO remains contraindicated in patients with a risk of bleeding because of systemic anticoagulation during the treatment. The most important point is controlling th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Indeed, there are several reports of heparin-free ECMO implementation in trauma patients, without significant related complications, using higher blood flow, to avoid thrombosis of the circuit. 9 Our patient was transfused with eight red blood cell units during ECMO support, which is consistent with the reported blood transfusion strategies in VV-ECMO. 10 Another concern of ECMO use in immunocompromised patients is the risk of infections associated with insertion of cannulas.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, there are several reports of heparin-free ECMO implementation in trauma patients, without significant related complications, using higher blood flow, to avoid thrombosis of the circuit. 9 Our patient was transfused with eight red blood cell units during ECMO support, which is consistent with the reported blood transfusion strategies in VV-ECMO. 10 Another concern of ECMO use in immunocompromised patients is the risk of infections associated with insertion of cannulas.…”
Section: Discussionsupporting
confidence: 88%
“…Extended advanced monitoring is suggested to detect early deterioration, ideally as a baseline before initiation of ECMO to prevent potentially deleterious bleeding or thromboembolic complications [ 201 , 202 ]. Using extracorporeal lung assist has been reported in various circuit compositions, with all of these reports describing feasibility without an increased risk of bleeding and survival benefits, as well as high survival rates [ 161 , 162 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 ]. Some authors even reported using it in severe bleeding situations [ 158 , 216 , 217 , 218 ].…”
Section: Factors Excluded As Contraindications/additional Contraindications Onlymentioning
confidence: 99%
“…Using extracorporeal lung assist has been reported in various circuit compositions, with all of these reports describing feasibility without an increased risk of bleeding and survival benefits, as well as high survival rates [ 161 , 162 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 ]. Some authors even reported using it in severe bleeding situations [ 158 , 216 , 217 , 218 ]. To gain the greatest benefit, a decision to initiate ECMO should not be delayed [ 209 , 213 , 214 , 219 ].…”
Section: Factors Excluded As Contraindications/additional Contraindications Onlymentioning
confidence: 99%
“…[8][9][10][11] There are successful reports of prolonged heparin-free ECMO use in patients with trauma as well as other pathologies that retain a high risk of bleeding complications. 4,12 Due to the debate of ECMO's role in trauma, a retrospective study was proposed at our center, which has both a high level of ECMO and trauma expertise. The objective of this study was to assess the use of VV ECMO in the trauma patient population to determine mortality and complication rates.…”
Section: Introductionmentioning
confidence: 99%